An expert system for float management / Nuraini Rejab - Rejab, Nuraini (1992)
The objective of this study is to generate a computer programme which apply 'Expert System* to be used by site engineers in making better decision in utilizing free time or float available in non-critical activities. The programme has been developed using an expert system shell ie LEORNARDO. The knowledge acquisition for this study has been the combination of expert advice, textbooks and journals. Nine major areas or factors have been identified in this study which is the basis in developing the rules ie. float duration, activity duration, possibility of slippage, crew completeness, safety, client requirement, degree of complexity, supervisory requirement and precedence activity. The float management programme developed has been found to be in good operational condition upon a few "dummy" test carried out.